Preliminary monitoring results of total coliforms and fecal coliform in the Red river system, in the section from Yen Bai to Hanoi - Bich Ngoc, Nguyen Thi; Thuy, Nguyen Bich; Mai Huong, Nguyen Thi; An, Vu Duy; Thuy, Duong Thi; Cuong, Ho Tu; Phuong Quynh, Le Thi (Academia Journal of Biology, 2014)
The paper presented the initial results of total coliforms (TC) and fecal coliform (FC) in the Red River system, the section from Yen Bai city to Hanoi city in the period from January to December 2013. The results showed that TC and FC densities varied in a high range: TC from 23 to 13,000 MPN/100 ml, and FC from 0 to 1,600 MPN/100 ml. Almost TC and FC values ​​were lower than the allowed limits of the QCVN 08-2008 column A2 for TC and column B1 for FC. However, at some observed time, TC values were recorded to exceed 2.2 to 2.6 times over the allowed limits column A2 and FC values exceeded from 1.5 to 16 times over the column B1. The high TC and FC densities in the Red River system can influence indirectly and/or directly to the human health due to the use of river water as drinking water, irrigation and aquaculture. Thus, the results underlined the need for regular monitoring of the Red River water quality, especially TC and FC, for different purposes of river water use as actual. The results also revealed that in the upstream river (from Yen Bai to Son Tay), TC and FC were clearly affected by the diffuse source whereas in the downstream part (section through Hanoi), they were affected by the point-source in its basin. So, there should be some effective solutions to manage and treat the waste sources in the Red River basin.